On Prodi–Serrin type conditions for the 3D Navier–Stokes equations. (January 2020) - Pineau, Benjamin; Yu, Xinwei
Abstract: In this paper we prove several new Prodi–Serrin type regularity criteria with weak Lebesgue integrability in both space and time for the 3D Navier–Stokes equations in the whole space.